High-Average-Power Polarization Maintaining All-Fiber-Integrated Nonlinear Chirped Pulse Amplification System Delivering Sub-400 fs Pulses - Hailong Yu; Pengfei Zhang; Xiaolin Wang; Pu Zhou; Jinbao Chen (IEEE Photonics Journal, 2016)
We experimentally demonstrate a monolithic single polarization nonlinear chirped pulse amplification (CPA) system producing high-average-power femtosecond pulses operating at 1.06 $μ\text{m}$ . Thanks to the fiber-based components and standard fiber splicing techniques, the system is nearly fully fiberized, except for the bulk grating pulse compressor. The main fiber amplifier delivers chirped picosecond pulses with average power of 193 W, repetition rate of 80 MHz, and duration of 209 ps. The pulse compressor is designed using high line density transmission gratings to keep small grating separation for the consideration of compactness and simplicity. After pulse compression, femtosecond pulses with average power of 119 W, duration of 352 fs, and peak power of 4.2 MW are obtained. The compression efficiency is 61.5%, limited by the diffraction efficiency of transmission gratings. Even so, to our knowledge, this is the highest average power ever reported in fiber CPA systems with a fiber-based stretcher. The mismatched third-order dispersion between fiber stretcher and bulk optical grating compressor is successfully compensated via optimization of the total nonlinear phase shift in the fiber amplifier chain.